2000
DOI: 10.1046/j.1462-2920.2000.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a chromium‐reducing bacterium from a chromated copper arsenate‐contaminated site

Abstract: A Gram-negative bacterium (CRB5) was isolated from a chromium-contaminated site that was capable of reducing hexavalent chromium to an insoluble precipitate, thereby removing this toxic chromium species from solution. Analysis of the 16S rRNA from the isolate revealed that it was a pseudomonad with high similarity to Pseudomaonas synxantha. CRB5 was tolerant to high concentrations of chromate (500 mg l(-1)) and can reduce Cr(VI) under aerobic and anaerobic conditions. It also exhibited a broad range of reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 20 publications
(34 reference statements)
7
38
0
1
Order By: Relevance
“…Arthrobacter sp. SUK 1201 cells reduced 100 M Cr(VI) in 48 h when the initial cell concentration was maintained at 10 9 cells/mL; however, with 10 fold increase in cell density, 100 M Cr(VI) was completely reduced in 30 h. Increase in cell density stimulated Cr(VI) reduction process (Table 2) as has been reported with Bacillus sphaericus AND 303 [28], Pseudomonas CRB5 [29], Ochrobactrum intermedium SDCr-5 [30], Lysinibacillus fusiformis ZC1 [25], and Arthrobacter sp. SUK 1205 [27].…”
Section: Effect Of Initial Cell Density Reduction Of Cr(vi)supporting
confidence: 67%
“…Arthrobacter sp. SUK 1201 cells reduced 100 M Cr(VI) in 48 h when the initial cell concentration was maintained at 10 9 cells/mL; however, with 10 fold increase in cell density, 100 M Cr(VI) was completely reduced in 30 h. Increase in cell density stimulated Cr(VI) reduction process (Table 2) as has been reported with Bacillus sphaericus AND 303 [28], Pseudomonas CRB5 [29], Ochrobactrum intermedium SDCr-5 [30], Lysinibacillus fusiformis ZC1 [25], and Arthrobacter sp. SUK 1205 [27].…”
Section: Effect Of Initial Cell Density Reduction Of Cr(vi)supporting
confidence: 67%
“…However, we cannot exclude that the extremely small amount of DNA obtained from these samples biases the total number of predicted species. Both library 1 and library 3 contain sequences closely related to Pseudomonas synxantha, which is a known reducer of Cr(VI) as well as a hydrocarbon degrader, pointing toward a potential involvement in bioremediation (23,28,51). Overall, our data show that MDA can be used to obtain enough DNA from low-biomass samples to evaluate their microbial diversity.…”
Section: Vol 72 2006mentioning
confidence: 79%
“…Whole cells of IFR-2 and IFR-3 reduced 24 and 30% of the initial Cr(VI) concentration (1 mg/l) in 45 min respectively. Initial cell density has been shown to have a dramatic effect on Cr(VI) reduction [16]. A number of factors may be contributing to the observed trends, including Cr(VI) toxicity acclimation time needed to readjust cells to low nutrient loads before initiation of reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Optimal Cr(VI) reduction was shown to be directly related to the optimum pH (8.0) for the growth of Bacillus isolates [4]. McLean et al [16] reported a wide range of pH between 6.0 to 9.0 for Cr(VI) reduction by P. synxantha.…”
Section: Resultsmentioning
confidence: 99%